Anxiety and theory of mind: A moderated mediation model of mindfulness and gender - BİLİCİ, MUSTAFA (My University, 2022)
This study aimed to examine the relationship between gender, anxiety, mindfulness, and theory of mind (ToM). It was also aimed to investigate the mediating role of mindfulness in the relationship between anxiety and ToM. Additionally, the moderating role of gender in the relevant relationships was examined. The sample consisted of 323 people, including 260 (80.5%) females and 63 (19.5%) males, aged between 18-62 years. Data were collected by the Reading the Mind in the Eyes Test, the State-Trait Anxiety Inventory II, and the Mindful Attention Awareness Scale. It was found that ToM and anxiety levels were statistically significantly higher in women than men. In the regression analysis, it was detected that mindfulness predicts the 7% variance in ToM. The second predictor of ToM was found as anxiety, and both predictors explained the 9% variance in ToM. In the mediating analysis, it was found that mindfulness has a mediating role in the relationship between anxiety and ToM. In the moderated mediation analysis, it was determined that the pathway between anxiety and ToM was moderated by gender; the moderating role of gender also was found between mindfulness and ToM. In light of these findings, experimental future studies can be suggested with clinical samples for a better understanding of the relationships between gender, anxiety, mindfulness, and ToM.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; PSİKOLOJİ, MULTİDİSİPLİNER; Temel Bilimler (SCI); PSYCHOLOGY, MULTIDISCIPLINARY; PSYCHOLOGY; Natural Sciences (SCI); General Psychology; Psychology (miscellaneous); Social Sciences & Humanities; anxiety; gender; mindfulness; theory of mind; EMOTION REGULATION; EYES TEST; DEPRESSION; DISORDER; INTERVENTIONS; CHILDREN; DEFICITS; AUTISM; SCALE; SCHIZOPHRENIA; anxiety; gender; mindfulness; theory of mind